Environmentally assisted crack growth in adhesively bonded composite joints. (November 2017) - Tracy, Jared; Yin, Yikai; Yang, Jeffrey; Osborne, John C.; Blohowiak, Kay Y.; Dauskardt, Reinhold
Abstract: Adhesively bonding composite components is a reliable alternative to conventional joining processes that minimizes part weight and reduces fabrication costs. Regarding performance and reliability, of particular interest is developing adherend surface treatments that enhance adhesion of the joint interfaces in aggressive chemical environments. Using fracture mechanics-based adhesion metrologies, critical and subcritical crack growth were evaluated for several peel-ply-treated, adhesively bonded composite joints. Fracture toughness, Gc, and corresponding failure modes were evaluated for specimens constructed using two different bonding processes (co-bonding and secondary bonding) and four different peel ply treatments. Environmentally assisted crack growth was evaluated as a function of time in several environments: humid, high temperature humid, and hydraulic fluid immersion. It is shown that humid environments accelerate crack growth rates, da/dt, relative to the strain energy release rate, G. This effect was amplified at elevated temperatures and further amplified in the presence of hydraulic fluid.